Specificity of lipoprotein lipase binding to endothelial cells. - MF Stins; P Sivaram; A Sasaki; IJ Goldberg (Journal of Lipid Research, 1993)
Lipoprotein lipase (LPL) hydrolyzes circulating lipoprotein triglyceride molecules while it is associated with the luminal surface of capillary endothelial cells. The precise molecular mechanism by which LPL attaches to these cells is unknown. LPL and a number of other molecules, including growth factors and clotting factors, bind to heparin-affinity gels and are eluted using high concentrations of salt. Of these molecules, antithrombin III and basic fibroblast growth factor have been shown to bind to specific cell surface heparan sulfate proteoglycans. Recent data from our laboratory (Sivaram et al. 1992. J. Biol. Chem. 267: 16517-16522) have shown that a heparin-sensitive, non-proteoglycan 116-kDa LPL-binding protein is present on cultured bovine aortic endothelial cells (BAEC). A series of experiments was performed to study the specificity of LPL binding to BAEC and to this 116-kDa protein. At low amounts of LPL (1 microgram) 125I-labeled LPL binding to the cells was inhibited up to 82% by the addition of a 20-fold excess of unlabeled LPL. LPL binding to the BAEC was not decreased by the addition of similar amounts of either antithrombin or thrombin. Specific LPL binding was eliminated by incubating the BAEC at 4 degrees C with heparin containing buffer prior to the addition of LPL. Although cellular internalization of 125I-labeled LPL at 37 degrees C was decreased when an excess of each of the three proteins was added to the culture medium, LPL was most effective. Furthermore, when LPL interaction with the 116-kDa binding protein was studied using ligand blots, 125I-labeled LPL binding was blocked only by unlabeled LPL.(ABSTRACT TRUNCATED AT 250 WORDS)